Totality the great American eclipses of 2017 and 2024 - Littmann, Mark 1939-; Espenak, Fred (Oxford University Press, 2017)
A complete guide to solar eclipses for the general public with detailed coverage of the 2017 and 2024 total eclipses over the U.S. Well timed for the August 2017 eclipse over North America, it shows how, when, and where to see the coming total solar eclipses, how to photograph and video record them, and how to do so safely....
Includes bibliographical references (pages 329-337) and index
Keywords: SCIENCE / Astronomy / bisacsh; Solar eclipses / fast / (OCoLC)fst01124979; Solar eclipses; SCIENCE / Astronomy; Sonnenfinsternis